Water flux prediction of UV-photografted nanofiltration membrane for forward osmosis application - Ahmad Fikri Hadi, Abdul Rahman; Siti Nudra Shafinie, Ab Aziz; Mazrul Nizam, Abu Seman (Institute of Physics Publishing, 2020)
In the application of forward osmosis, commercial nanofiltration (NF) membrane was modified via ultraviolet(UV)-photografting technique at different grafting parameters; monomer concentration (acrylic acid) and grafting time. However, the performance of the modified membrane measured at the osmotic pressure of 1M NaCl as draw solution limits their applications. In this research, the mathematical modelling was applied to predict the water flux at different osmotic pressure. The mathematical modelling indicated that the generated water flux follows the osmotic pressure but strictly affected by the grafting parameters. The result shows that at grafting time of 3min, the monomer concentration of 15 g/L generates the highest water flux followed by the membrane modified at the monomer concentration of 30 g/L. High water flux was attributed to the presence of strongly hydrophilic groups at new carboxyl layers leading to improved membrane properties. The approach of theoretical modelling on the membrane that is reported in this work allows estimating the water flux at different grafting parameter.